2016
DOI: 10.18805/lr.v39i4.11258
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diverse treatments on biophysical characteristics of red kidney beans

Abstract: The effect of line, tempering solution, temperature and soaking time were investigated on water absorption, splitting, and texture of two Iranian red kidney beans including Akhtar and Derakhshan to determine the best line and the best soaking conditions for industrial use. Akhtar line showed higher level of water absorption in comparison to Derakhshan line. Water absorption of unblanched red beans at 2.5 hour soaking was two times greater than water absorption of blanched ones for both lines (p<0.05). Acid sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This finding could be due to the capability of EDTA to chelate different minerals from the seed coats and/or to degrade proteins constituents in the seed coat membranes percolating free amino into the boiling water of cooking media. It has been shown that high ionic strength anions in EDTA are thought to denature protein and then shortening the cooking times [ 19 ]. This decrease in the amino acid content diminishes the nutritional value of V. faba beans and emphasis the importance of finding alternative ways for a healthy and efficient cooking process.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be due to the capability of EDTA to chelate different minerals from the seed coats and/or to degrade proteins constituents in the seed coat membranes percolating free amino into the boiling water of cooking media. It has been shown that high ionic strength anions in EDTA are thought to denature protein and then shortening the cooking times [ 19 ]. This decrease in the amino acid content diminishes the nutritional value of V. faba beans and emphasis the importance of finding alternative ways for a healthy and efficient cooking process.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the proteins are degraded into non-immunogenic peptides while travelling through GI tract, but some proteins may escape and enter enteric vasculature and cause allergy (Sampson, 2004). One of the mechanisms which helps them to escape may include aggregation, which occurs after exposing to high temperature (Zamindar et al, 2016). For instance, vicilin becomes resistance to proteolytic digestion after exposing to high temperature (Beyer et al, 2001;Mankotia and Modgil, 2016).…”
Section: Introductionmentioning
confidence: 99%